The Effect of Mesenchymal Stem Cells Transplantation on Cardiac Functioning and Contractility in Experimental Myocardial Infarction - S. I. Estrin; T. V. Kravchenko; A. O. Kovalchuk (Ukrainian Journal of Cardiovascular Surgery, 2021)
Introduction. Heart failure as a result of ischemic myocardial remodeling is one of the most severe diseases with poor prognosis. Drug therapy alone with surgical or percutaneous revascularization of damaged myocardium often fails to achieve optimum effect in the treatment of the mentioned syndrome. Cell cardiomyoplasty using autologous bone marrow derived mesenchymal stem cells (BM-MSCs) has already proved to be promising alternative to both these treatment methods, as it’s aimed directly at restoration of normally functioning myocard.The aim. To study the effects of different techniques of cardiomyoplasty with BM-MSCs on morphometrical and functional indices of post-infarctional left ventricular remodeling in experiment.Materials and methods. An experimental model of myocardial infarction in laboratory rats was used for the research. The survived animals were equally divided into 5 groups; the animals of 3 groups underwent BM-MSC transplantation. A certain technique of cardiomyoplasty was used in each of the 3 groups: direct injection into necrotic myocardium, intravenous injection and injection inside left ventricular cavity (which imitates intracoronalintroduction). Other 2 groups were comparison groups where the animals did not achieve BM-MSCs after infarction. There was also control group with intact animals with normal values of all the studied indices. The following invasive and noninvasive measurements of functional heart indices have been done in all research groups: left ventricular weight and its relation to body weight, end-systolic and end-diastolic left ventricular internal dimensions, fractional shortening, ejection fraction, stroke volume, heart rate, systemic arterial pressure and left ventricular inner pressure, both systolic and diastolic. The follow-up period was 1 and 3 months after the experiment. Finally, all animals were euthanized and autopsied, and the results of macroscopic examination of their hearts have been matched with aforecited functional indices in each group.Results and discussion. The analysis of all measured parameters and their comparison between groups have revealed that BM-MSC transplantation (irrespective of technique) conduces to reliably significant retention of functioning myocardium volume, reliably significant improvement of contractility parameters, particularly, reduced end-systolic and end-diastolic internal dimensions, increased ejection fraction, fractional shortening and stroke volume; it also contributes to maximal inalterability of such hemodynamic parameters as heart rate, systemic arterial pressure, left ventricular inner pressure. In addition, in all 3 groups of cell therapy the indices of contractility and pump function of the left ventricle were very close to normal rates. But the optimal results have been obtained in the group of direct intramyocardial injections.Conclusion. Cell cardiomyoplasty with BM-MSCs tends to prevent ischemic myocardial remodeling and, as a result, to improve myocardial contractility and neutralize manifestations of severe heart failure in short-term follow-up of 1 and 3 months.